ROLE OF DIETARY SUPPLEMENTATION IN PREVENTING PROGRESSION OF AGE-RELATED MACULAR DEGENERATION - N. A. Ermakova (Oftalʹmologiâ)
Age-related macular degeneration (AMD) is a chronic, progressive, degenerative eye disease affecting the central retina. It is the leading cause of blindness among individuals of 65 years and older. In the early stage patients have drusen and/or alterations of pigmentation in the macular region. This disease can progress to geographic atrophy and/or choroidal neovascularization. It has been shown that oxidative stress and hypoxia are important in the pathogenesis of AMD. Patients may gain some visual improvement with inhibitors of vascular endothelial growth factor, but complete restoration of visual function is achieved only in small cases. No effective therapies are known for atrophic AMD. Many large observational studies have shown that dietary antioxidant supplementation is beneficial in preventing the progression of AMD from early to late stages. The Age-Related Eye Disease Study (AREDS) demonstrated that daily oral supplementation with vitamins C (500 mg) and E (400 IU), beta carotene (15 mg), zinc (80 mg) and copper (2 mg) reduced the risk of progression to advanced AMD by 25% at 5 years. In primary analyses AREDS II failed to show further reduce of this risk by addition of lutein (10 mg) and zeaxanthin (2mg), or/and omega-3 long-chain polyunsaturated fatty acids [docosahexaenoic acid (350 mg DHA) and eicosapentaenoic acid 650 mg (EPA)] to the AREDS formulation. But there was no true placebo group. The simultaneous administration of beta carotene, lutein and zeaxanthin may suppress tissue level of the both laters because of competitive absorption of carotenoids. Subgroup analyses revealed that dietary supplementation with lutein, zeaxanthin and AREDS formulation without beta carotene may reduce the risk of progression to advanced AMD.The LUNA (Lutein nutrition effects measured by autofluorescence) study demonstrated that supplementation with lutein (12 mg), zeaxanthin (1 mg), vitamin C (120 mg), vitamin E (17,6 mg), zinc (10 mg), selenium (40 mg) resulted in a significant augmentation of macular pigment optical density (MPOD). This effect was more prominent in cases with initial low level of MPOD. The CARMA (Carotenoids in Age-Related Maculopathy) Study has shown that lutein (6 mg), zeaxanthin (0,3 mg), vitamin C (75 mg), vitamin E (7,5 mg), zinc (10 mg) and copper (0,2 mg) prevented progression from early to late stages of AMD. Early intervention is more effective in maintaining visual function.